Pemetaan Kawasan Rawan Bencana Banjir dan Penentuan Jalur Evakuasi dengan Metode Network Analysis di Kecamatan Sangatta Utara - Aswad Janfari, Al; Hidayat, Arief; Yorika, Rahmi; Mustofa, Umar (Fakultas Teknik Universitas Bosowa, 2024)
This study aims to map the flood evacuation route in North Sangatta District. Several analyzes were used in this study to achieve the objectives to be achieved, first of all analyzing the level of vulnerability to floods in North Sangatta District by using the overlay method. In determining the route used network analyst method. Based on the results of the analysis that has been done, it is found that the level of vulnerability to flooding is divided into three, namely low, medium and high. Evacuation routes obtained 22 evacuation route directions with 9 evacuation location points.